Modulation of the Hyperglycemia Condition in Diabetic Lab Rats with Extracts of the Creole Jamaica Flower (Hibiscus sabdariffa L.) from the Morelia Region (Mexico) - Teodoro Suárez-Diéguez; Marta Palma-Morales; Gloria Isabel Camacho Bernal; Erick Noe Valdez López; Celia Rodríguez-Pérez; Nelly del Socorro Cruz-Cansino; Juan Antonio Nieto (MDPI AG, 2024)
Extracts from Jamaica flowers (Hibiscus sabdariffa) from Morelia (Mexico) were evaluated as antidiabetic ingredients in a diabetic rat lab model for 80 days at doses of 200, 400, and 600 mg extract/kg rat weight. The hydroalcoholic extract (water:ethanol 80:20 (v/v) at 50 °C) showed a TPC value of 403.28 ± 7.71 mg GAE/g extract, and an antioxidant activity of 0.219 ± 0.00003 mmol Trolox/g (ABTS) and 0.134 ± 0.00001 mmol Trolox/g (DPPH). The extract allowed reducing the diabetic glucose plasma levels under fasting conditions in a dose-dependent manner by 35.2%, 41.63%, and 50.1%. Additionally, the highest dose of the extract (600 mg/kg) slightly reduced the short-term postprandial glucose response while improving the long-term response, reducing hyperglycemia by 45.1%. The same dose also improved lipid metabolism by reducing total cholesterol, triglycerides, VLDL, and LDL, while the HDL level increased. The improvement in glucose and lipid management in the treated groups also led to reduced levels of glycosylated hemoglobin, as well as lower insulin resistance (TyG index), compared to the diabetic control group. The results of this study suggest that extracts from Hibiscus sabdariffa (Morelia) can be used as potential functional ingredients or nutraceuticals for managing the diabetic condition.